PENGARUH PENYULUHAN KEBERSIHAN TANGAN TERHADAP PERILAKU CUCI TANGAN PADA SISWA DI SD NEGERI 9 TULEHU - Rasni; Nielma Likliwatil; Novita Lenony Ruhukail (Pasapua Health Journal, 2020)
Introduction: Hand washing is the process of mechanically removing dirt and dust from the skin of both hands using soap and water. As a result of a lack of hand washing habits, children are the highest sufferers of diarrheal and respiratory diseases, so that it often leads to death. The purpose of this study was to determine the effect of hand hygiene counseling on hand washing behavior in students at SD Negeri 9 Tulehu. Method: The design of this study used a pre-experimental design with a one-group pre-test-post test design. It was a study with one group of subjects who underwent treatment/intervention, which were measured before and after treatment. The population in this study were all 5th grade students at SD Negeri 9 Tulehu as many as 45 students using a total sampling technique. Results: The results of the study were obtained from 24 respondents where the hand washing behavior of students at SD Negeri 9 Tulehu, before being given counseling (28.9%) had a rare hand washing behavior and (71.1%) had a frequent hand washing behavior. Whereas after being given counseling the respondents (11.1%) had a rare hand washing behavior and (88.9%) had a frequent hand washing behavior. From the results of data analysis using the Wilcoxon statistical test, significant results were obtained with a value of p = 0.021 <0.05, which means that Ho was rejected and Ha was accepted, namely that there was an effect of hand hygiene counseling on hand washing behavior in students at SD Negeri 9 Tuehu. Suggestions: that can be conveyed in connection with this research are that counseling about hand washing should be carried out routinely in schools.